Independence of Early Childhood in Implementing Clean and Healthy Living Behaviors at the Foot of Mount Merapi - Erny Ermawati; Reni Pawestuti Ambari Sumanto (Universitas Pendidikan Ganesha, 2025)
The implementation of clean and healthy living behaviors has an impact on children's growth and development. Independence is one of the urgent needs in the implementation of clean and healthy living behaviors, especially in disaster-prone areas such as the foot of Mount Merapi. This study aims to analyze the independence of early childhood in the implementation of clean and healthy living behaviors at the foot of Mount Merapi. Data collection was conducted using observation, interviews, and documentation of five research subjects: children aged 3-5 years, parents, close family members, and teachers. The results of the study showed that children aged 3-5 years demonstrated positive independence in the implementation of clean and healthy living behaviors, both at home and at school. Three out of five children were independent in washing their hands, both at home and at school. Additionally, three out of five children were also independent in using toilets at home. All five children demonstrated independence in disposing of waste, consuming healthy food and drinks, and balancing sleep/rest needs with activities at home. At school, all children have demonstrated independence in the indicators of using healthy toilets, disposing of waste, consuming healthy food and drinks, and balancing rest and activities. The implications of this research can serve as a foundation for teachers, parents, and policymakers to design curriculum and environment-based interventions, particularly in disaster-prone areas, to ensure that children's independence in Clean and Healthy Living Behavior continues to develop and supports their health and resilience in facing environmental risks.